Surveillance of Aflatoxin and Microbiota Related to Brewer's Grain Destined for Swine Feed in Argentina - Gisela A. Gerbaldo; Carina M. Pereyra; Lilia R. Cavaglieri; Francisco Ruiz; Liliana Pascual; Ana M. Dalcero; Isabel L. Barberis (Veterinary Medicine International)
Córdoba province in the center of Argentina is an important area of swine production. The use of industry by-product (brewer's grain) as feedstuff for swine is a regular practice and increases animal performance on these animals production. The occurrence of aflatoxin contamination is global, causing severe problems especially in developing countries. No reports on aflatoxin B1 production, micoflora, and potential aflatoxin B1 producing microorganism from brewer's grain are available. The aims of this study were (1) to isolate the microbiota species from brewer's grain, (2) to determine aflatoxin B1 natural contamination levels, and (3) to determine the ability of Aspergillus section Flavi isolates to produce aflatoxins in vitro. Physical properties, total fungal counts, lactic acid bacteria, and fungal genera distribution were determined on this substrate. In 65% of the samples, fungal counts were higher than recommended by GMP, and lactic bacterium counts ranged from 1.9×105 to 4.4×109 CFU g−1. Aspergillus spp. prevailed over other fungal genera. Aspergillus flavus was the prevalent species followed by A. fumigatus. Aflatoxin B1 levels in the samples were higher than the recommended limits (20 ng g−1) for complementary feedstuffs. Several Aspergillus section Flavi strains were able to produce aflatoxin B1  in vitro. Inadequate storage conditions promote the proliferation of mycotoxin-producing fungal species. Regular monitoring of feeds is required in order to prevent chronic and acute toxic syndromes related to this kind of contamination.